Learn to Sail in a Weekend - Driscoll, John (John P.) (London Dorling Kindersley, 1991)
Part of a series that offers a concentrated course for the beginner, which is intended to be completed in 48 hours. This book outlines the basic terms and techniques of sailing and outlines more advanced techniques. Other books in the series include "Tennis" and "Golf".
Include Index, Glossary and Illustration
Keywords: Sailing -- Boats and boating